Mental health state in medical students during COVID-19 pandemic - Dian Natalia; Rizma Adlia Syakurah (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Before the COVID-19 pandemic, medical students had reported experiencing high rates of distress, burnout, anxiety, and depression. The psychological impact of the COVID-19 in the general population suggested that the mental health impact was increased anxiety, depression, and stress. There were no exceptions if medical students also experience the same psychological impact. The aimed to this study is analyze the mental and emotional effects of the COVID-19 pandemic among medical students. MATERIALS AND METHODS: An observational analytic study was used with a cross-sectional approach. Data were obtained with questionnaires distributed through social media platforms from July 14, 2020, to July 21, 2020. This study using the Fear of COVID-19 (FCV-19) Scale and the Depression, Anxiety, and Stress Scale-21 to assess FCV-19, anxiety, stress, and depression. statistical analysis used IBM SPSS Statistics 24 was used to analyze the two-tailed Chi-square test, the Mann-Whitney test, and the Kruskal-Wallis test, which were used with statistical significance as P < 0.05 for all tests. RESULTS: Out of 1027 samples, 44.6% had stressed, 47.8% had anxiety, and 18.6% had depression. The gender (P = 0.000), educational stage (P = 0.000), and the comorbidity factor (P = 0.001 for stress and anxiety, P = 0.036 for depression, and P = 0.000 for FCV-19) had a significant association with stress, anxiety, depression, and FCV-19 in medical students. The hometown that showed zone risk of infection only showed significant differences in FCV-19 (P = 0.026). CONCLUSIONS: Protection and psychological support for a medical student is extremely high importance given that COVID-19 is now a well-established pandemic and there will be other pandemics in the future.